Catalisadores a base de Cu, Ni e Mg suportados em Al2O3 aplicados à gaseificação de etanol em meio contendo água em condições supercríticas - Melo, Jarbas Almeida de (2018)
In this work the synthesis of catalysts was carried out with the objective of H2 production from gasification of ethanol in medium containing water under supercritical conditions. Based on reports from the literature, Cu, Ni and Mg were selected as components for the active phase, alumina (Al2O3) as catalysts support. The catalysts were prepared from aqueous solutions of nitrate salts precursors of Cu, Ni and Mg. The catalysts were characterized by X-ray fluorescence (FRX), scanning electron microscopy, thermogravimetric and thermal differential analysis (TG/ATD), X-ray diffraction (DRX) and textural analysis by N2 adsorption / desorption isotherms at -196 ° C. The TG/ATD analysis indicated that the calcination of the catalytic precursors was sufficient for the removal of water and decomposition of the nitrates of the metal salts precursors of the active phase. In the FRX analysis, the increase in the concentration of the metals in relation to the nominal values after the synthesis of the catalysts was characterized, with an increase of 20 to 40% depending on the metal due to the loss of water from the alumina support. The FRX analysis of the catalysts used in the catalytic tests shows that there was no significant leaching during the gasification process. DRX analysis have characteristic results that the metals are in amorphous form or dispersed in the form of small crystallites. Textural analysis of N2 adsorption / desorption isotherms indicated a reduction of approximately 60% in the specific surface area between the alumina and the calcined alumina and the specific area values between the alumina and the metal catalysts were kept close. The catalytic tests were performed at a pressure of 25 MPa and at temperatures of 400 to 650 ° C. A 10/1 molar water / ethanol solution was fed. In the catalytic tests H2, CH4, CO, CO2, C2H4, C2H6, C2H4O were obtained. The highest ethanol conversions were obtained at the temperature of 650 ° C for the catalysts NiO/Al2O3 and NiO-MgO/Al2O3, both 81%. The highest yield was 0.41 mol H2 / mol ethanol fed to the NiO / Al2O3 catalyst, at a temperature of 600 ° C. The highest selectivity at the temperature of 600 ° C was 39%, obtained by the NiO/Al2O3 catalyst.